Dampak Ekspor Impor di Indonesia Saat Covid-19 - Salsabila, Muthia Nur; Sulistiawan, Naila Anggun; Irawan, Ryu Habibah (PT Maju Malaqbi Makkarana, 2024)
This study aims to understand the impact of export and import activities when the Covid-19 virus occurs. This study uses a qualitative approach. To determine the impact, we used monthly data on worldwide trade from January 2019 to August 2020. In 2o2o, the Covid-19 virus took the world by storm along with mobility restriction policies in each country, resulting in constrained export and import activities. From data we obtained, we found a significant negative impact of Covid-19 on international trade in both exporting and importing countries. The impact of Covid-19 in importing countries has become. Insignificant since July 2020. From the research results, Covid-19 resulted in impacts such as: (1) There was decrease in import volume in Indonesia which occurred in 2020 in February and May; (2) Because of Covid-19, document processing must take longer and must carry out health protocols for all export and import activities; (3) Imposters must provide more costs for the arrival of their goods because most ships experience delays in handling at the port.